THE STUDY OF NEUROMEDIATORY ACTION OF THE COMBINATION DRUG “MEMOFIT” UNDER CHRONIC IMMOBILIZATION STRESS - Savelieva E. V.; Vladimirova I. M.; Kulikova O. V.; Tishakova T. S.; Butko Ya. O. (Scientific Journal of Pedagogy and Economics, 2019)
Neuromediatory action of the combination drug “Memofit” has been studied using the parameters of lipid peroxidation products and antioxidant system. POL and antioxidant system were determined by marker indicators: specifically, the level of primary oxidation products – diene conjugates and secondary products – malonic dialdehyde; anti-oxidative systems; catalase activity and superoxide dismutase. Experimental research has been performed in 18 WAG rats with approximate body weight from 210 to 230 g. Stress-modeling action has been studied on the model of neuromuscular tension during 5, 15 and 30 days. Immobilization stress was modeled by keeping rats for 5 hours in plastic cages – plastic boxes. Blood serum was used for investigation. Level of primary oxidation products – diene conjugates (DC) and secondary products – malonic dialdehyde (MDA) and state of antioxidant system has been determined by spectrophotometric method. Based on the POL level parameters, we can make a conclusion, that the tested combination drug “Memofit” decreases TBA-AP and DC parameters only on the 30-th day statistically significant in relation to immobilization stress and reaches to control. The level of catalase at immobilization stress + combination drug “Мемоfit” is 4.12±0.09 c.u., correspondently, that is statistically significant in relation to the group of animals, that were subjected to immobilization stress 6.23±0.03 c.u. (Р<0.05). The level of SOD at immobilization stress + combination drug “Memofit” reaches 4.16±0,09 c.u. correspondently, that is statistically significantly in relation to immobilization stress 7.13±0.89 c.u. and control 3.59±0.11 (Р<0.05).